Pelatihan Manajemen Keuangan dan Pemasaran pada UKM Lebah Sempage melalui Pelatihan Akuntansi Sederhana dan Digital Marketing - Febriana, Widia; Fahry; Anggriani, Rini; Komala, Rina; Rahman, Haikal Fikri (Insan Kreasi Media, 2024)
Sempage Bee SMEs (Small and Medium Enterprises) have great potential for growth, but often face challenges in financial management and marketing. The training was designed to improve the SMEs' financial management and marketing capacity through two main approaches: simple accounting and digital marketing training. The simple accounting training aimed to provide a basic understanding of neat and structured financial records, making it easier for businesses to manage cash flow, prepare financial reports, and make data-based decisions. Meanwhile, the digital marketing training focused on utilizing technology and digital platforms such as social media, e-commerce, and online marketing strategies to expand market reach and improve product competitiveness. The results of this training showed an increase in participants' ability to manage finances and utilize digital media for marketing. In addition, the training also opened up opportunities for collaboration and innovation in SME business development. Thus, this activity is expected to become a sustainable SME empowerment model that is relevant to the needs of the digital era.